The Use Of Mirtazapine As A Hypnotic - Francisca Magalhães Scoralick; Einstein Francisco Camargos; Otávio Toledo Nóbrega (Geriatrics, Gerontology and Aging)
Prescription of approved hypnotics for insomnia decreased by more than 50%, whereas of antidepressive agents outstripped that of hypnotics. However, there is little data on their efficacy to treat insomnia, and many of these medications may be associated with known side effects. Antidepressants are associated with various effects on sleep patterns, depending on the intrinsic pharmacological properties of the active agent, such as degree of inhibition of serotonin or noradrenaline reuptake, effects on 5-HT1A and 5-HT2 receptors, action(s) at alpha-adrenoceptors, and/or histamine H1 sites. Mirtazapine is a noradrenergic and specific serotonergic antidepressive agent that acts by antagonizing alpha-2 adrenergic receptors and blocking 5-HT2 and 5-HT3 receptors. It has high affinity for histamine H1 receptors, low affinity for dopaminergic receptors, and lacks anticholinergic activity. In spite of these potential beneficial effects of mirtazapine on sleep, no placebo-controlled randomized clinical trials of mirtazapine in primary insomniacs have been conducted. Mirtazapine was associated with improvements in sleep on normal sleepers and depressed patients. The most common side effects of mirtazapine, i.e. dry mouth, drowsiness, increased appetite and increased body weight, were mostly mild and transient. Considering its use in elderly people, this paper provides a revision about studies regarding mirtazapine for sleep disorders.